Abdominal neoplastic manifestations of neurofibromatosis type 1. (25th June 2020) - Dare, Anna J; Gupta, Abha A; Thipphavong, Seng; Miettinen, Markku; Gladdy, Rebecca A
Abstract: Neurofibromatosis type 1 (NF1) is an autosomal dominant hereditary tumor syndrome, with a wide clinicopathologic spectrum. It is defined by characteristic central nervous system, cutaneous and osseous manifestations, and by mutations in the NF1 gene, which is involved in proliferation via p21, RAS, and MAP kinase pathways. Up to 25% of NF1 patients develop intra-abdominal neoplastic manifestations including neurogenic (commonly plexiform neurofibromas and malignant peripheral nerve sheath tumors), interstitial cells of Cajal (hyperplasia, gastrointestinal stromal tumors), neuroendocrine, and embryonal tumors (rhabdomyosarcoma). Nonspecific symptoms, multifocal disease, or coexistence of 2 or more tumor types make patients challenging to diagnose and manage. Screening for intra-abdominal tumors in NF1 patients remains controversial, and currently no guidelines are established. Management decisions are complex and often informed by single-center experiences or case studies in the literature, though the field is rapidly evolving. Thus, NF1 patients should be followed in specialist centers familiar with their wide spectrum of pathology and with multidisciplinary care including specialized pathology and radiology. This review will (1) provide a contemporaneous synthesis of the literature and our multi-institutional clinical experiences with intra-abdominal neoplasms in NF1 patients, (2) present a classification framework for this heterogeneous group of disorders, and (3) outline approaches to screening, surveillance, diagnosis, and management.